THE INFLUENCE OF STRUCTURED QUESTIONS IN TEACHING WRITING DESCRIPTIVE PARAGRAPH TO THE EIGHTH GRADE STUDENTS OF MTS AL HUDA KARANG MELATI - Andriani, Dwi; Sartini, Sartini
The objective of the research was to find out whether or not there was a significant different between students who were taught by using structured questions in teaching writing descriptive paragraph and those who were not taught at the eighth grade students of MTs Al Huda Karang Melati. In this research the writer used experimental method, quasy experimental design. The population of this research were 84 students and sample were 60 students by using purposive sampling. The finding of this research, the result of the post test score of control and experimental class used independent t-test. And the result of the calculation showed that t-obtained was higher than t-table (6.52 > 2,021). It means that there was any significant difference between experimental and control class. So, the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. As a conclusion, there was a significant different between students who were taught by using structured questions in teaching writing descriptive paragraph and who were not taught (conventional strategy).